Co-designing a virtual reality game for alcohol prevention. (13th November 2019) - Stock, C; Vallentin-Holbech, L; Dietrich, T; Majgaard, G
Abstract: Issue/problem: Health promotion programmes that train social competencies in situations adolescents commonly encounter are likely to minimise the social influence and social pressure to drink or use other substances. In the Virtual Reality (VR) TestLab project, an innovative VR learning tool is developed that shows a typical party situation for young people. The game user can navigate through the party making their own choices, which result in different outcomes. Description of the problem: The Living Lab method guided the development of the VR learning tool. During the four phases of the Living Lab process three groups of 16-25-year-old students were involved, as well as two prevention practitioners, three prevention scientists, three VR game designers and one film production expert. Results: At the initial exploration stage of the Living Lab framework a list of key concepts/scenes were co-created with all stakeholders. At the concept stage students were invited to co-create a film script for the VR game. The prototype stage involved students as actors for the scenes, which were then finally recorded in technical collaboration with game developers and the film production expert. Post production, the finalised scenes were integrated into a game engine to develop the interactive branching narrative. At the innovation stage the group was invited to examine, explore and test its usability and share their experiences, thoughts, and attitudes. Lessons: The Living Lab framework was useful in order to structure the co-creation process into meaningful phases and to ensure that all stakeholders were consulted throughout the development of the VR game. The Living lab framework gave 'voice' for the end-users (young people and practitioners) to actively engage in the co-creation process. Main message: This first Living Lab application in drug prevention contributes to a better understanding of the importance of involving users of health promotion products and services through co-creation.